Facilitators and barriers for home-based monitoring to time frozen embryo transfers in IVF among women and healthcare providers. Issue 3 (30th May 2022) - Zaat, T R; de Bruin, J P; Mol, F; van Wely, M
Abstract: STUDY QUESTION: What are the facilitators and barriers concerning the implementation of home-based monitoring for natural cycle frozen embryo transfer (NC-FET) from the perspectives of patients and healthcare providers in the Netherlands? SUMMARY ANSWER: The most important facilitator was optimal pregnancy chance for both the patients and healthcare providers, and the most important barriers were the risk of missing an ovulation for the patients and laboratory capacity for the healthcare providers. WHAT IS KNOWN ALREADY: The share of FET cycles in IVF treatments is increasing and, therefore, it is important to optimize protocols for FET. Monitoring of ovulation, which is used in NC-FET, can be hospital-based (ultrasounds and ovulation triggering) or home-based (LH urine tests). Home-based monitoring has the advantage of being the most natural protocol for FET and provides the feeling of empowerment and discretion for patients. A systematic approach for the implementation of home-based monitoring has to start with an exploration of the perspectives of all stakeholders. STUDY DESIGN, SIZE, DURATION: Stakeholders (patients and healthcare providers) involved in the implementation process in the Netherlands participated in the present study. Patients were represented by the Dutch Patient Organisation for Couples with Fertility Problems (FREYA) and healthcare providers were represented by gynaecologists and their society (The Netherlands Society of Obstetrics and Gynaecology), embryologists and their society (The Dutch Federation of Clinical Embryology) as well as fertility doctors. A panel of experts hypothesized on barriers and facilitators for the implementation of home-based monitoring during the proposal phase of the Antarctica-2 randomized controlled trial (RCT). PARTICIPANTS/MATERIALS, SETTING, METHODS: All stakeholders were represented during the study. Two different questionnaires were developed in order to investigate facilitators and barriers for the patients and for healthcare providers. The facilitators and barriers were ranked on a scale of 1–10 with 10 being the most important. Based on our power analysis, we aimed for a minimum of 300 completed questionnaires for the patients and a minimum of 90 completed questionnaires for the healthcare providers. Facilitators and barriers were analysed using frequencies, mean (SD) and ranking. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 311 patients filled out the questionnaire of whom 86.8% underwent FET previously. The most important facilitator for the patients was to implement the strategy with the highest chance of pregnancy (mean 9.7; 95% CI 9.6–9.7) and the most important barrier was risk of missing ovulation (mean 8.4; 95% CI 8.2–8.6). A total of 96 healthcare providers filled out the questionnaire. According to healthcare providers, patients would accept the strategy when it causes less interference with their work and private life (mean 7.5; 95% CI 7.1–8.0) and has a low risk of missing the ovulation (mean 7.6; 95% CI 7.1–8.0). The most important facilitator for the implementation of home-based monitoring for healthcare providers was optimizing cumulative pregnancy rates (mean 8.1; 95% CI 7.7–8.4) and the most important barrier was the lack of laboratory capacity and flexibility (mean 6.4; 95% CI 5.8–7.0). LIMITATIONS, REASONS FOR CAUTION: Facilitators and barriers were selected based on expert opinion. Currently, there are no validated questionnaires that aim to assess facilitators and barriers for the implementation of treatments in fertility care. WIDER IMPLICATIONS OF THE FINDINGS: During our study, we gained insight into barriers and facilitators for the implementation of home-based monitoring of NC-FET at an early phase. Early sharing and discussion of the results of this study with all stakeholders involved should stimulate a fast incorporation in guidelines, especially as key professionals in guideline development took part in this study. Also, based on our results, we can advise guideline developers to add tools to the guideline that may help overcome the implementation barriers. STUDY FUNDING/COMPETING INTERESTS: The Antarctica-2 RCT is supported by a grant from the Netherlands Organisation for Health Research and Development (ZonMw 843002807). No authors have any competing interests to declare. TRIAL REGISTRATION NUMBER: Trial NL6414 (NTR6590).